Association between serum albumin and peripheral arterial disease in hypertensive patients. Issue 12 (9th October 2020) - Ding, Congcong; Wang, Hua; Huang, Xiao; Hu, Lihua; Shi, Yumeng; Li, Minghui; Yu, Yu; Zhou, Wei; Wang, Tao; Zhu, Lingjuan; Bao, Huihui; Cheng, Xiaoshu
Abstract: The authors aimed to evaluate the relationship of serum albumin with peripheral arterial disease (PAD) and investigate any possible effect modifiers in hypertensive patients. In the cross‐sectional study, a total of 10, 900 Chinese hypertensive patients aged ≥18 years were enrolled. The outcome was PAD, defined as an ankle‐brachial index (ABI) <0.90 in either leg. The overall mean (SD) serum albumin was 46.8 (4.2) g/L. There were significant inverse associations of serum albumin with PAD (per SD increment; OR: 0.83; 95% CI: 0.72, 0.94). Compared with the lowest tertile (<45.1 g/L), the multivariate‐adjusted ORs (95% CI) for participants in the middle tertile (45.1‐48.2 g/L) and highest tertile (≥48.2 g/L) of serum albumin were 0.89 (95% CI: 0.67, 1.16) and 0.65 (95% CI: 0.47, 0.90), respectively. Conversely, lower albumin (<48.2 g/L) concentrations were associated with increased odds of PAD (OR: 1.45; 95% CI: 1.08‐1.96) compared with higher concentrations. Furthermore, the albumin–PAD association was significantly stronger in males (OR: 2.08; 95% CI: 1.31, 3.30) than in females (OR: 1.06; 95% CI: 0.70, 1.58; p interaction = .024). In conclusion, among Chinese hypertensive adults, lower serum albumin was associated with the prevalence of PAD only in males but not in females.